Exploring the Core Dimension of Curriculum for Inclusive Education in the Division of Nueva Ecija - Sebastian, Ethel Joy V (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The Philippine education system is progressively stressing Inclusive Education, with the Department of Education (DepEd) supporting programs that cater to varied student requirements. This study assesses the extent of implementation of the Inclusive Education Framework (IEF) in Special Education (SpEd) schools across ten key dimensions. data was collected from 30 SpEd school administrators in Nueva Ecija, Philippines. Findings reveal disparities in school profiles, with varying enrollment sizes, faculty qualifications, and facility access. Regarding IEF implementation, dimensions like Curriculum, Learning Delivery, and Assessment show high implementation levels. However, areas like Learning Environment, Partnerships, and Governance Support require improvement. The study underscores the need for continuous evaluation and enhancement to ensure a fully inclusive education system.